Diversifikasi Produk Susu Sapi Lokal melalui Pengolahan Keju Mozzarella dan Soft Candy di Ciawi, Bogor - Irma Isnafia Arief; Nurul Hidayati; Zaenal Abidin; Tjut Awaliyah Zuraiyah (Institut Pertanian Bogor, 2026)
Ciawi, Bogor, represents a region with high potential in the agricultural sector, particularly dairy farming, where approximately 20% of local farmers are engaged in milk production. This condition provides opportunities for developing home industries that transform cow’s milk into value-added products. In response, Institut Pertanian Bogor (IPB), as a leading educational and research institution in Indonesia, has collaborated with PT. Bogor Sari Nutrisi (a local MSME/ Micro, Small and Medium Entreprises) and CV. Wahyu Farm Sejahtera (a dairy farm) to establish a program aimed at producing mozzarella cheese and soft candy from locally sourced cow’s milk. The project was implemented through a comprehensive situational analysis of local challenges and opportunities, dissemination of university-based innovations to industry, and collaborative partnerships with local enterprises. The initiative has resulted in improvements in production capacity and product quality, positioning mozzarella cheese and soft candy as potential regional specialty products. These findings demonstrate that innovation in milk processing can enhance the added value of local agricultural commodities, expand market opportunities, and contribute positively to regional economic development.